Tirbanibulin Attenuates Pulmonary Fibrosis by Modulating Src/STAT3 Signaling - Wang, Xin; Ren, Rui; Xu, Zehui; Huang, Haidi; Jiang, Wanglin; Ma, Jinbo (Frontiers in Pharmacology, 2021)
Tirbanibulin (KX-01) is the first clinical Src inhibitor of the novel peptidomimetic class that targets the peptide substrate site of Src providing more specificity toward the Src kinase. This study assessed the impact of KX-01 on cobalt chloride (CoCl2)-treated L929 cells and bleomycin (BLM)-induced pulmonary fibrosis in rats to evaluate the efficacy of this compound in vitro and in vivo, respectively. In CoCl2-treated L929 cells, KX-01 significantly reduced the expression of smooth muscle actin (α-SMA), collagen I, collagen III, hypoxia inducing factor (HIF-1α), signal transducers and transcriptional activators (p-STAT3), and p-Src. In BLM-induced pulmonary fibrosis rats, KX-01 reduced pathological scores, collagen deposition, α-SMA, collagen I, collagen III, p-Src, HIF-1α, and p-STAT3. Overall, these findings revealed that KX-01 can alleviate experimental pulmonary fibrosis via suppressing the p-SRC/p-STAT3 signaling pathways.